2023
DOI: 10.3389/fnagi.2023.1230467
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of medium chain fatty acids in aging and neurodegenerative disease

Ella Dunn,
Biqin Zhang,
Virender K. Sahota
et al.

Abstract: Neurodegenerative diseases are a large class of neurological disorders characterized by progressive dysfunction and death of neurones. Examples include Alzheimer’s disease, Parkinson’s disease, frontotemporal dementia, and amyotrophic lateral sclerosis. Aging is the primary risk factor for neurodegeneration; individuals over 65 are more likely to suffer from a neurodegenerative disease, with prevalence increasing with age. As the population ages, the social and economic burden caused by these diseases will inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 233 publications
0
3
0
Order By: Relevance
“…Studies conducted on humans have reported that oils rich in MCTs and MCTs themselves can induce satiety and modulate proteins involved in lipid metabolism to ameliorate disorders related to lipid metabolism and weight gain [30]. Furthermore, MCTs have been utilized in the treatment of various neurological disorders like epilepsy and Alzheimer's disease within the ketogenic diet [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on humans have reported that oils rich in MCTs and MCTs themselves can induce satiety and modulate proteins involved in lipid metabolism to ameliorate disorders related to lipid metabolism and weight gain [30]. Furthermore, MCTs have been utilized in the treatment of various neurological disorders like epilepsy and Alzheimer's disease within the ketogenic diet [31].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Ketogenic diet: The benefits of fasting can potentially be obtained by following a ketogenic diet characterized by low carbohydrate intake and a high proportion of fat, which is thought to mimic certain aspects of starvation by inducing a shift in whole-body metabolism toward increased fat oxidation and the production of ketone bodies [37]. There are various types of ketogenic diets 4 : 1, 3 : 1, 2 : 1 based on the lipid: carbohydrate ratio [38].…”
Section: Strategies To Modulate Beta-hydroxybutyratementioning
confidence: 99%
“…MCT is an alternative type of ketogenic diet that relies on the premise that medium-chain fatty acids such as octanoic acid (also known as caprylic acid) and decanoic acid (also known as capric acid) are metabolized into ketone bodies more efficiently and allow a more palatable diet with higher consumption of carbohydrates [ 40 ]. During an MCT diet, 30–60 percent of the calories are obtained from MCT oil or emulsion and 30 percent from long-chain dietary fats.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%